Albumin is encoded by 2 messenger RNAs in Xenopus laevis. - Schoenberg, D R (1981)
A cDNA clone library was prepared from liver poly(A) RNA pf non-estrogenized Xenopus laevis. Albumin coding sequences were screened by hybridization to a cDNA prepared from poly(A) RNA enriched by sucrose density gradient centrifugation, and by a sensitive solid-phase radioimmunoassay to detect clones that contain templates for albumin antigenic determinants. Nine clones were obtained by this approach, and all but one have the cDNA inserted in phase with the beta-lactamase gene of pBR322. Mapping of these clones with restriction endonucleases yielded 2 distinct patterns, suggestive of heterogeneity in the coding sequences. This was confirmed by heteroduplex analyses of hybrids formed between clones representative of each of the 2 classes. Both classes of albumin cDNA clones were used to select mRNAs of the same size (2.3kb) that code for peptides that are indistinguishable by SDS gel electrophoresis. Examination of the organization of the albumin genes by blot hybridization of the cDNA clones to restriction fragments of Xenopus DNA failed to detect any differences at the genomic level. The considerable diversity of the albumin cDNAs is suggestive of a multiplicity of albumin genes, rather than differential processing of a common precursor RNA.